The Impact of a High-risk Sexual Behavior Prevention Program via Mobile Application on Sexual Knowledge and Attitude of Female Students - Elnaz Dehghani; Fatemeh Erfanian; Talat Khadivzadeh; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2019)
Background & aim: The prevalence of high-risk sexual behaviors among different social groups has been considered as a serious health-related threat in recent years. Given the importance of raising awareness and health among the youth and preventing high-risk behaviors, the present study was conducted to investigate the effect of a high-risk sexual behavior prevention program via mobile application on sexual knowledge and attitude in undergraduate female students. Methods: This quasi-experimental study was conducted among two groups of female students with a pretest-posttest design. A total number of 200 undergraduate eligible female students of Mashhad University of Medical Sciences, Mashhad, Iran were recruited in 2016. The subjects were randomly assigned to an intervention group receiving education through a mobile application (N=100) and a control group (N=100). To collect data a self-structured demographic questionnaire as well as sexual knowledge and attitude questionnaires were used. In the intervention group, the participants received a prevention program through a mobile application. Knowledge and attitude towards high-risk sexual behaviors were assessed and compared before and two weeks after the intervention. To analyze the data, paired t-test, independent t-test, Mann-Whitney U test, Wilcoxon signed-rank test, and Chi-square test were run in SPSS, version 16. Results: The mean scores of sexual knowledge and attitude after education increased compared to the pre-intervention stage (p0.05). Conclusion: The study results reflected the favorable effect of education via mobile application. The implementation of high-risk sexual behavior prevention programs using mobile applications could enhance sexual knowledge and attitude in students and promote community health